Pengaruh Pemberian Buklet Bacaan Islami Dengan Penerimaan Diri Pasien Hemodialisis - Agus Prasetyo; Sodikin Sodikin; Sarwa Sarwa (Universitas Faletehan, 2020)
Patients undergoing hemodialysis experience various problems arising from malfunctioning of the kidneys. They are 1.5 to 3 times more likely to experience psychological disorders than other chronic diseases including low levels of self-acceptance. This study aims to determine the effects of giving Islamic reading booklets on self-acceptance of hemodialysis patients at Islamic Hospital of Fatimah Cilacap. This study used a quasi-experimental design. The type of this research is one group pre-test-post-test design. The study was conducted to 52 patients undergoing hemodialysis at Islamic Hospital of Fatimah Cilacap with a purposive sampling technique. The instrument of patient self-acceptance scale in this study is a questionnaire that consists of 15 question items and had been tested for validity and reliability. The data analysis used sample paired T Test. The results showed that most samples are female (55.4%); most length of hemodialysis period is in the range of 1-3 years (57.7%); most patients’ educational background is elementary school (46.2%); the mean of patients’ age is 49.86 years. The Sig. (2-tailed) value is 0.000 <0.05; in other words, there are effects of giving Islamic reading booklets on hemodialysis patients’ self-acceptance at Islamic Hospital of Fatimah Cilacap.